2016
DOI: 10.1007/s10578-016-0669-9
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ Early Depressive Symptoms and Preschoolers’ Behavioral Problems: The Moderating Role of Genetic Influences

Abstract: As a stressful environment in families, mothers' depressive symptoms might increase children's risks of developing behavioral problems by exacerbating genetic influences. Using data from the nationally representative Early Childhood Longitudinal Study-Birth Cohort data of approximately 750 pairs of twins, we examined whether genetic influences on preschoolers' behavioral problems depended upon mothers' depressive symptoms. Results indicated that the genetic etiology for both internalizing and externalizing beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
2
1
0
Order By: Relevance
“…Alternately, the children may have developed these attributes as a way of navigating the stress of harsh parenting. However, these results are also consistent with the differential susceptibility theory, which posits that some individuals are more sensitive to environment (both positive and negative) than others (Belsky & Pluess, 2009;Yan, Benner, Tucker-Drob, & Harden, 2017). In line with this hypothesis, we found greater genetic variance at the extreme end of environmental experience (i.e.…”
Section: Discussionsupporting
confidence: 91%
“…Alternately, the children may have developed these attributes as a way of navigating the stress of harsh parenting. However, these results are also consistent with the differential susceptibility theory, which posits that some individuals are more sensitive to environment (both positive and negative) than others (Belsky & Pluess, 2009;Yan, Benner, Tucker-Drob, & Harden, 2017). In line with this hypothesis, we found greater genetic variance at the extreme end of environmental experience (i.e.…”
Section: Discussionsupporting
confidence: 91%
“…The studies we have just summarized of the moderating influence on parenting of genetically influenced child effects bring us several steps closer to a mechanistic understanding of the importance of Gene × Environment interactions. First, we affirm previous findings from twin and adoption studies that genetic moderation of environmental influences are plentiful during the toddler period; this pattern reinforces and corroborates a modest number of prior adoption and twin studies in early childhood that have also demonstrated these effects (e.g., Plomin et al, 1988; Tucker‐Drob & Harden, 2013; Yan et al, 2017).…”
Section: Overall Summary Of This Chaptersupporting
confidence: 88%
“…The etiology of behavioral disorders is understood to involve the interaction of multiple environmental and genetic risk and protective factors (Pennington, 2006), and as such, maternal characteristics may link to child behavior through genetic and/or environmental means. Maternal depression, for example, is understood to have a negative impact on children's emotional, cognitive, and behavioral development, effected through both shared genetic risk and environmental factors (Mars et al, 2012;Natsuaki et al, 2010;Rice et al, 2017;Yan, Benner, Tucker-Drob, & Harden, 2017), balanced against protective factors (Collishaw et al, 2016). Children of depressed mothers have higher levels of psychopathology, behavioral, and social adjustment difficulties (Billings & Moos, 1983;Carter, Garrity-Rokous, Chazan-Cohen, Little, & Briggs-Gowan, 2001;Dietz, Jennings, Kelley, & Marshal, 2009;Goodman et al, 2011;Luoma et al, 2001;Murray & Cooper, 1997), as well as higher irritability, lower responsiveness, less engagement in social relationships, and a more limited range of affect (Carter et al, 2001).…”
mentioning
confidence: 99%